Las ferias agroalimentarias de Costa Rica espacios para promocionar la agroindustria, los productos típicos y el turismo en los territorios rurales - Blanco, Marvin (2012)
In order to analyze the characteristics and the impact of agri- food fairs on the commercialization of agricultural products, agro-industrial production and development of tourism in rural areas, we conducted a preliminary investigation of four of the fairs held in Costa Rica: avocado, orange, peach palm fruit, and cheese. The results show that fairs have a level of organization simple but flexible and committed to compliance with the various activities. They are located in open areas of 800 m2 on average as squares, fairgrounds or communal streets, where the product that gives its name to the fair is sold at various stands, along with agro-industrial products, handicrafts, other agricultural products, plants and typical meals. These events have positive results on the generation of employment and income and create linkages and social ties between local producers, rural communities, and visitors. In addition, the fairs promote rural tourism helping to diversify the local economy. Also it was found that there are problems of local organization, limited infrastructure and lack of clarity about the objectives and purposes of the fairs.